2009
DOI: 10.3201/eid1507.081256
|View full text |Cite
|
Sign up to set email alerts
|

Chinese-like Strain of Porcine Epidemic Diarrhea Virus, Thailand

Abstract: Since late 2007, several outbreaks of porcine epidemic diarrhea virus (PEDV) infection have emerged in Thailand. Phylogenetic analysis places all Thai PEDV isolates during the outbreaks in the same clade as the Chinese strain JS-2004-2. This new genotype PEDV is prevailing and currently causing sporadic outbreaks in Thailand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
161
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(171 citation statements)
references
References 7 publications
6
161
2
2
Order By: Relevance
“…Among the six genes of CH/ FJND-3/2011, the S gene has the lowest sequence identity (93.75%) with that of CH/S and is 9 nt longer than those of CV777 and CH/S. The PEDV S gene plays an important role in the molecular epidemiology of PEDV in the field and in the genetic variation of PEDV field isolates (3,4,5). The alignment in the S1 region (nt 1 to 2217) of the S gene reveals two domains exhibiting increased divergence compared to the remaining part of the sequence.…”
mentioning
confidence: 99%
“…Among the six genes of CH/ FJND-3/2011, the S gene has the lowest sequence identity (93.75%) with that of CH/S and is 9 nt longer than those of CV777 and CH/S. The PEDV S gene plays an important role in the molecular epidemiology of PEDV in the field and in the genetic variation of PEDV field isolates (3,4,5). The alignment in the S1 region (nt 1 to 2217) of the S gene reveals two domains exhibiting increased divergence compared to the remaining part of the sequence.…”
mentioning
confidence: 99%
“…The disease was initially recognized in England in 1971, but the causative agent of this disease, PED virus (PEDV), was identified in 1978 [3]. PED epidemics were first reported in Asia in 1982, and since then, PED has continued to threaten swine health, causing substantial economic losses in the Asian swine industry [4][5][6]. In 2013, PED outbreaks suddenly occurred in the United States and have swept through the pork industry across the country, raising concerns about control measures for PED prevention [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The disease was first recognized in Correspondence to: R.F. Li, e-mail: lirenfeng@sina.com England in 1971 (Pensaert et al 1978), and since then, outbreaks have been reported in Europe and Asia (Bridgen et al 1993, Puranaveja et al 2009, Chen et al 2010, and more recently in the United States (Wang et al 2014). In China, although a periodic vaccination strategy has been applied nationwide to control the disease in pig farms, PEDV outbreaks have continued to occur causing large financial losses in the Table 1.…”
Section: Introductionmentioning
confidence: 99%